State of the art and challenges in bioprinting technologies - Fermeiro, João Bernardo Lopes (2014)
The rapid growth of world’s population and the increase in human life expectancy has been leading to a lack of organs for transplant. Data from WHO leads to a crescent concern about this issue, because the organ demand largely exceeds the organ supply, an as consequence there has been an unethical exploitation from wealthier countries over poorer, disadvantaged populations. In the search to overcome this problem Tissue Engineering has appeared and is the scientific area where most research is being made. Some of the most important strategies in Tissue Engineering will be addressed and discussed in this work, to show its limitations and advances to reach the ultimate goal of producing a viable tissue for implantation. There is one which will be more focused, called bioprinting and its most important methods will be described and compared for a better look at what really is bioprinting. In an attempt to recreate the research being done worldwide in this area, a bioprinter was built with good resolution and precision for bioprinting testing. The bioprinter was built from ground up, with a simple design and with low cost materials, without compromising its capability. For the bioprinter control an algorithm was created, in Matlab environment and in the used microcontroller, with the capability to analyse and treat images for posterior printing.